Writing Theory during a Pandemic - Florêncio, João (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): João Florêncio Title (English): Writing Theory during a Pandemic Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 32-34 Page Count: 3 Citation (English): João Florêncio, “Writing Theory during a Pandemic,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 32-34.